Ultraviolet-curable resin composition, light-emitting device, and method for manufacturing light-emitting device

By using a low viscosity ultraviolet curable resin composition, the problem of excessive viscosity of optical lens materials during molding is solved, and the high light extraction efficiency and low light reflection effect of the optical device are achieved.

JP7627836B2Active Publication Date: 2025-02-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020147127
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-27
Filing Date
2020-09-01
Publication Date
2025-02-07
Estimated Expiration
2040-09-01

AI Technical Summary

Technical Problem

The optical lens materials in the prior art have too high viscosity during the molding process, resulting in poor molding properties of the mold and easy light reflection, affecting the light extraction efficiency of the optical equipment.

Method used

A low viscosity ultraviolet curable resin composition is employed, which comprises a photopolymerization component and a photopolymerization initiator, with a viscosity not exceeding 30 mPa·s at 25°C or 40°C, and cured by ultraviolet irradiation to form an optical component to reduce light reflection and improve light extraction efficiency.

Benefits of technology

The high mold moldability of the low viscosity optical resin composition during the molding process and the high light extraction efficiency of the optical equipment are achieved, reducing light reflection and improving the optical performance of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627836000004
    Figure 0007627836000004
  • Figure 0007627836000001
    Figure 0007627836000001
  • Figure 0007627836000002
    Figure 0007627836000002
Patent Text Reader

Abstract

To provide an ultraviolet curable resin composition which can maintain low viscosity and prevents reflection of light.SOLUTION: An ultraviolet curable resin composition contains a photopolymerizable component (A) and a photopolymerization initiator (B). A refractive index of the ultraviolet curable resin composition is 1.53 or more. A viscosity at at least one temperature of 25°C and 40°C of the ultraviolet curable resin composition is 30 mP s or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an ultraviolet-curable resin composition, a light-emitting device, and a method for manufacturing a light-emitting device, and in particular to an ultraviolet-curable resin composition for producing optical components, a light-emitting device including an optical component made of a cured product of this ultraviolet-curable resin composition, and a method for manufacturing a light-emitting device. [Background technology]

[0002] Light-emitting devices equipped with light-emitting elements such as light-emitting diodes are used for illumination, displays, and the like, and are expected to become even more widespread in the future.

[0003] Among light-emitting devices, those called top emission type are constructed by, for example, disposing a light-emitting element on a support substrate, disposing a transparent substrate facing the support substrate, and filling the space between the support substrate and the transparent substrate with a transparent sealant. In this case, the light emitted by the light-emitting element can be emitted to the outside through the sealant and the transparent substrate.

[0004] For example, Patent Document 1 discloses a photocurable high refractive index resin composition containing a (meth)acrylate component, a photopolymerization initiator, zirconia fine particles, and an organosilicon compound. It is disclosed that this photocurable high refractive index resin composition contains a (meth)acrylate component having a fluorene skeleton, thereby achieving a high refractive index and providing excellent adhesion of a layer made from the resin composition to a substrate. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-19245 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, although the photocurable high refractive index resin composition disclosed in Patent Document 1 can achieve a high refractive index, the viscosity of the resin composition becomes too high when the resin composition is molded, making it difficult to ensure sufficient moldability.

[0007] An object of the present disclosure is to provide an ultraviolet-curable resin composition that can maintain a low viscosity and reduce the occurrence of light reflection, a light-emitting device including an encapsulant made of a cured product of this ultraviolet-curable resin composition, and a method for manufacturing the light-emitting device. [Means for solving the problem]

[0008] The ultraviolet-curable resin composition according to one embodiment of the present disclosure contains a photopolymerizable component (A) and a photopolymerization initiator (B). The refractive index of the ultraviolet-curable resin composition is 1.53 or more. The viscosity of the ultraviolet-curable resin composition at at least one of 25°C and 40°C is 30 mP·s or less.

[0009] A light emitting device according to an aspect of the present disclosure includes a light source and an optical component that transmits light emitted from the light source. The optical component includes a cured product of the ultraviolet curable resin composition.

[0010] A method for manufacturing a light-emitting device according to one embodiment of the present disclosure is a method for manufacturing a light-emitting device including a light source and an optical component that transmits light emitted by the light source, and includes forming the ultraviolet-curable resin composition by an inkjet method, and then irradiating the ultraviolet-curable resin composition with ultraviolet light to cure it, thereby producing the optical component. Effect of the Invention

[0011] According to one aspect of the present disclosure, an ultraviolet-curable resin composition can be obtained that can maintain a low viscosity and is less likely to cause light reflection.

[0012] Moreover, according to one aspect of the present disclosure, a light emitting device capable of having excellent light extraction efficiency can be obtained. [Brief description of the drawings]

[0013] [Figure 1] Fig. 1A is a schematic cross-sectional view showing a first example of a light emitting device according to an embodiment of the present disclosure, and Fig. 1B is a schematic cross-sectional view showing a second example of a light emitting device according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, one embodiment of the present disclosure will be described.

[0015] Conventionally, when producing an optical component from a resin composition, in order to increase the refractive index of the optical component, particles with a high refractive index, such as inorganic particles, are blended into the resin composition. In this case, a cured product is produced by curing the resin composition, and the optical component made of this cured product can have a high refractive index. If the refractive index of the optical component can be increased, the efficiency of extracting light from a device such as a light-emitting device equipped with a light-emitting element can be improved.

[0016] However, when a resin composition contains particles with a high refractive index, this can affect the viscosity of the resin composition and can also adversely affect the moldability (inkjetability) when the resin composition is molded by inkjet.

[0017] Therefore, the inventors conducted extensive research to obtain an ultraviolet-curable resin composition having a composition that has good ink-jet properties and is capable of achieving a high refractive index in the resin composition and in the cured product thereof without relying on particles with a high refractive index, and arrived at the present invention.

[0018] That is, the ultraviolet-curable resin composition according to this embodiment (hereinafter also referred to as composition (X)) contains a photopolymerizable component (A) and a photopolymerization initiator (B). The refractive index of composition (X) is 1.53 or more. The viscosity of composition (X) at least one of 25°C and 40°C is 30 mP·s or less.

[0019] According to this embodiment, the composition (X) can be molded and then cured to be used as an optical component 5 in, for example, the light-emitting device 1, which transmits light emitted from a light source. That is, the optical component 5 is a component for transmitting light emitted from a light source such as a light-emitting element in a device having an optical system (for example, the light-emitting device 1). According to this embodiment, for example, a sealant 51 that covers the light-emitting element 4 in the light-emitting device 1 can be prepared as the optical component 5 (see FIG. 1A). Also, according to this embodiment, it is possible to prepare, as the optical component 5, a member (referred to as an adjustment layer 55 in FIG. 1B) that is provided on top of, for example, a passivation layer 61 in order to adjust the refractive index in the optical system in the light-emitting device 1.

[0020] The light-emitting device 1 shown as an example in FIG. 1A includes, for example, a light source, an optical component 5 that transmits light emitted by the light source, and an inorganic layer 6, and the optical component 5 and the inorganic layer 6 overlap. In particular, it is preferable to manufacture the sealant 51 of the light-emitting device 1 including the light-emitting element 4, the sealant 5 (51) that covers the light-emitting element 4, and the passivation layer 61 (62) that overlaps the sealant 51 from the composition (X). In this case, the sealant 51 is the optical component 5, the light-emitting element 4 is the light source, and the passivation layer 61 (62) is the inorganic layer 6 (see FIG. 1A). In this case, it is possible to prevent a decrease in luminous efficiency caused by the passivation layer 61 (62) and the sealant 51 in the light-emitting device 1. This is thought to be because the refractive index of the composition (X) is 1.53 or more, and therefore the refractive index of the optical component 5 made of the cured product of the composition (X) can be made close to the refractive index of the passivation layer 61 made of an inorganic material. By bringing the refractive index of the optical component 5 (e.g., the sealing material 51) closer to the refractive index of the passivation layer 61, it is possible to reduce the reflection of light at the interface between the sealing material 51 and the passivation layer 61, which is believed to increase the efficiency of extracting light emitted from the light-emitting element 4 to the outside.

[0021] 1B, when the light emitting device 1 includes an adjustment layer 55 as the optical component 5, it is considered that the refractive index of the adjustment layer 55 made of the cured product of the composition (X) can be made closer to the refractive index of the passivation layer 62 made of an inorganic material, thereby reducing the reflection of light at the interface between the adjustment layer 55 and the passivation layer 62. Details of the light emitting device 1 and the members constituting the light emitting device 1 will be described later.

[0022] In this embodiment, the refractive index of the composition (X) is 1.53 or more, so that when light emitted from a light source is emitted to an optical component containing a cured product of the composition (X), the degree of refraction of light inside the optical component can be reduced. In addition, reflection at the interface between the light incident on the optical component and a layer having a low refractive index overlapping the optical component when the light exits the optical component can be reduced. Here, in the present disclosure, the refractive index of the ultraviolet-curable resin composition (composition (X)) is the refractive index at 25°C for light with a wavelength of 589.3 nm (sodium D line).

[0023] The refractive index of the composition (X) is preferably 1.53 to 1.85, more preferably 1.58 to 1.80, and even more preferably 1.63 to 1.75. In this case, the refractive index of the optical component 5 made of the cured product of the composition (X) can be particularly close to the refractive index of the passivation layer 61 made of an inorganic material, and therefore the reflection of light at the interface can be particularly reduced.

[0024] The refractive index of the composition (X) is preferably 1.53 or more, so that the refractive index of the cured product of the resin composition (X) is preferably 1.53 or more. The refractive index of the cured product of the resin composition (X) is preferably 1.55 or more and 1.87 or less, more preferably 1.60 or more and 1.82 or less, and even more preferably 1.67 or more and 1.77 or less. Here, in the present disclosure, the refractive index of the cured product is the refractive index at 25°C for light with a wavelength of 589.3 nm (sodium D line).

[0025] Furthermore, in this embodiment, the viscosity of composition (X) at least one of 25° C. and 40° C. is 30 mP·s or less, so that the moldability of composition (X) can be improved. Therefore, composition (X) can be easily molded by the inkjet method at room temperature in particular.

[0026] The viscosity of composition (X) at 25° C. is more preferably 25 mPa·s or less, even more preferably 22 mPa·s or less, and particularly preferably 18 mPa·s or less. It is also preferable that this viscosity is 4 mPa·s or more.

[0027] It is also preferable that the viscosity of the composition (X) at 40°C is 4 mPa·s or more and 30 mPa·s or less. In this case, no matter what the viscosity of the composition (X) at room temperature is, it is possible to lower the viscosity by slightly heating the composition (X). Therefore, by heating, the composition (X) can be easily molded by the inkjet method. In addition, since the viscosity of the composition (X) can be lowered without significantly heating it, it is possible to make it difficult for the composition of the composition (X) to change due to the volatilization of the components in the composition (X). It is more preferable that the viscosity is 25 mPa·s or less, even more preferable that the viscosity is 20 mPa·s or less, and particularly preferable that the viscosity is 15 mPa·s or less. It is also preferable that the viscosity is 5 mPa·s or more. The viscosity of the composition (X) is measured using a rheometer at a shear rate of 100 s -1 The measurement is performed under the following conditions. For example, a rheometer such as the model DHR-2 manufactured by Anton Paar Japan can be used.

[0028] Such a low viscosity of composition (X) at 25° C. or 40° C. can be achieved by the composition of composition (X) described in detail below. The viscosity of composition (X) may be 30 mPa s or less at both temperatures of 25° C. and 40° C.

[0029] The glass transition temperature of the cured product of the composition (X) is preferably 70°C or higher. In other words, the composition (X) preferably has the property of curing to become a cured product having a glass transition temperature of 70°C or higher. In this case, the cured product of the composition (X) can have good heat resistance. Therefore, for example, when the cured product is subjected to a treatment accompanied by an increase in temperature, the cured product is less likely to deteriorate. The glass transition temperature of the cured product of the composition (X) is more preferably 70°C or higher, even more preferably 80°C or higher, and particularly preferably 100°C or higher.

[0030] In this embodiment, the composition (X) is preferably formed by an inkjet method. In this case, it is easy to make the optical component 5 highly precise, that is, it is easy to manufacture the optical component 5 at a high density. Therefore, it is easy to improve the extraction efficiency of the light emitted by the light emitting element 4 of the light emitting device 1 including the light emitting element 4 and the optical component 5.

[0031] It is preferable that the composition (X) does not contain a solvent, or the content of the solvent (percentage of the solvent to the entire composition (X)) is 1 mass % or less. In this case, outgassing due to the solvent is unlikely to occur from the composition (X) and the cured product of the composition (X). Therefore, the viscosity change of the composition (X) due to the volatilization of the solvent is unlikely to occur. This can improve the storage stability of the composition (X). In addition, in the light-emitting device 1, when sealing the light-emitting element 4 with the optical component 5, it is possible to make it difficult for voids due to outgassing to occur in the optical component 5, and therefore, it is difficult for water to reach the optical component 5 through the voids, and the light-emitting element 4 is unlikely to deteriorate due to water. In addition, when producing the optical component 5 from the composition (X), a drying process for removing the solvent from the composition (X) and the cured product of the composition can be eliminated. There may be a drying process for removing the solvent from at least one of the composition (X) and the cured product, and in this case, it is possible to reduce at least one of the heating temperature and the heating time in the drying process. For this reason, outgassing from the optical component 5 can be suppressed without decreasing the production efficiency of the optical component 5. The content of the solvent is more preferably 0.5 mass % or less, further preferably 0.3 mass % or less, and particularly preferably 0.1 mass % or less. It is particularly preferable that the composition (X) does not contain a solvent or contains only a solvent that is unavoidably mixed in.

[0032] In this way, the composition (X) according to this embodiment can be used to prepare the encapsulant 51 in the light-emitting device 1 having the structure shown in FIG. 1A and FIG. 1B. That is, the composition (X) is used to prepare the encapsulant 51 for the light-emitting device 4 in the light-emitting device having the structure illustrated as a first example in FIG. 1A. In other words, the composition (X) is preferably a composition for preparing an encapsulant, a composition for sealing a light-emitting device, or a composition for manufacturing a light-emitting device. Also, the optical component 5 in the light-emitting device 1 having the structure illustrated as a second example in FIG. 1B can be prepared from the composition (X). That is, the composition (X) can also be used as a member (adjustment layer 55) for adjusting the refractive index of light emitted from the light-emitting device 4. In other words, the composition (X) can be preferably a composition for preparing an encapsulant, a composition for sealing a light-emitting device, and a composition for manufacturing a light-emitting device, and can also be said to be a composition for a refractive index adjusting member.

[0033] This embodiment will be described in further detail below.

[0034] 1. Ultraviolet curable resin composition The ultraviolet-curable resin composition (composition (X)) according to this embodiment will be described.

[0035] As described above, the composition (X) contains the photopolymerizable component (A) and the photopolymerization initiator (B). When the composition (X) is irradiated with ultraviolet light, a photoradical polymerization reaction is initiated by the photopolymerization initiator (B) and the photopolymerizable component (A) is cured, whereby a cured product of the composition (X) can be produced.

[0036] As described above, the composition (X) contains the photopolymerizable component (A).

[0037] The photopolymerizable component (A) has radical polymerizability. The photopolymerizable component (A) has, for example, one or more radically polymerizable functional groups in one molecule. The radically polymerizable functional group includes, for example, at least one selected from the group consisting of a vinyl group, a (meth)acryloyl group, an epoxy group, and an oxetane group. Note that an allyl group (CH2=CH-CH2-) is included in a vinyl group (CH2=CH-). In addition, in this embodiment, "(meth)acryl" means at least one of "acryl" and "methacryl". By having at least one functional group selected from these, the photopolymerizable component (A) can undergo a polymerization reaction when irradiated with light such as ultraviolet light.

[0038] The refractive index of the photopolymerizable component (A) is preferably 1.53 or more. In this case, the refractive index of the composition (X) and the cured product of the composition (X) can be easily brought closer to the refractive index of the layer made of an inorganic material (e.g., a passivation layer). This makes it easier to reduce the reflection of light at the interface between the passivation layer and the optical component 5 made of the cured product of the composition (X) that overlaps the passivation layer.

[0039] The viscosity of the entire photopolymerizable component (A) at 25°C is preferably 50 mPa·s or less. In this case, the photopolymerizable component (A) can particularly reduce the viscosity of the composition (X). The viscosity of the entire photopolymerizable component (A) is more preferably 30 mPa·s or less, even more preferably 25 mPa·s or less, and particularly preferably 20 mPa·s or less. The viscosity of the entire photopolymerizable component (A) is, for example, 3 mPa·s or more.

[0040] It is also preferable that the viscosity of the entire photopolymerizable component (A) at 40°C is 50 mPa·s or less. In this case, the photopolymerizable component (A) can particularly reduce the viscosity of the composition (X) when heated. The viscosity of the entire photopolymerizable component (A) is more preferably 30 mPa·s or less, even more preferably 25 mPa·s or less, and particularly preferably 20 mPa·s or less. In addition, the viscosity of the entire photopolymerizable component (A) is, for example, 3 mPa·s or more.

[0041] Components that may be contained in the photopolymerizable component (A) will be described below.

[0042] As described above, the refractive index of the composition (X) is 1.53 or more. In order to increase the refractive index of the composition (X), for example, it is preferable to include a compound with a high refractive index, particularly a compound with a refractive index of 1.53 to 1.85, in the photopolymerizable compound (A). The refractive index of this compound is more preferably 1.58 to 1.80, and even more preferably 1.63 to 1.75. The refractive index of this compound is the refractive index at 25°C for light with a wavelength of 589.3 nm (D line of sodium). Specifically, the photopolymerizable compound (A) contains at least one compound selected from the group consisting of a compound having an aromatic ring, a compound having a halogen atom other than fluorine, a compound having sulfur, and a compound having an alicyclic group. When at least one compound selected from the group consisting of an aromatic ring, a halogen atom other than fluorine, a sulfur atom, and an alicyclic group is introduced into the composition (X), the refractive index of the composition (X) and its cured product is likely to increase.

[0043] In particular, the photopolymerizable component (A) preferably contains a sulfur-containing compound (A1) having at least one sulfur atom in one molecule. The sulfur-containing compound (A1) also has photopolymerizability. Specifically, the sulfur-containing compound (A1) in this embodiment has a group having one or more unsaturated bonds in one molecule, and has at least one sulfur atom in one molecule. In this case, the sulfur-containing compound (A1) can contribute to increasing the refractive index of the composition (X). Therefore, the transmittance of the cured product of the composition (X) can be improved, and this can make it difficult to generate reflection at the interface between the optical component 5 containing the cured product of the composition (X) and a high refractive index layer overlapping the optical component 5. In addition, when the composition (X) contains the sulfur-containing compound (A1), it is possible to make it difficult to generate outgassing when curing the composition (X). Furthermore, in this case, the sulfur-containing compound (A1) can increase the adhesion between the cured product made of the composition (X) and the substrate. The group having an unsaturated bond includes, for example, at least one selected from the group consisting of a vinyl group and a (meth)acryloyl group.

[0044] The sulfur-containing compound (A1) preferably contains a compound having a refractive index of 1.53 or more and 1.85 or less at 25° C. The refractive index of this compound is more preferably 1.58 or more and 1.80 or less, and even more preferably 1.63 or more and 1.75 or less.

[0045] The sulfur-containing compound (A1) preferably contains a compound (A11) having an aryl sulfide skeleton. The compound (A11) also has photopolymerizability. Here, the aryl sulfide skeleton refers to a structure in which an aromatic ring and a sulfur atom are directly bonded with a single bond. The aromatic ring is, for example, a benzene ring (phenyl group), but is not limited to a benzene ring, and may be any hydrocarbon having aromaticity (for example, an aryl group). In addition, the hydrogen atom in the aromatic ring may be substituted with an atom other than a hydrogen atom or a functional group. The compound (A11) can easily suppress an excessive increase in viscosity by having an aryl group, and can contribute to improving the refractive index of the composition (X) by having a sulfur atom. Furthermore, the compound (A11) can easily achieve a low viscosity required for molding by the inkjet method by having an aryl group and a sulfur atom directly bonded. In addition, it is sufficient that at least one aryl group and at least one sulfur atom are chemically bonded to compound (A11). However, when compound (A11) has multiple aryl groups and multiple sulfur atoms, the aryl groups and sulfur atoms may be bonded alternately.

[0046] The compound (A11) preferably contains a compound having a structure represented by the following formula (1).

[0047] [ka]

[0048] In formula (1), R1 is an organic group. It is preferable that one or both of the two R1 are radically polymerizable functional groups. The radically polymerizable functional groups are as described above. That is, only one of the two R1 in formula (1), or each of the two R1, is at least one selected from the group consisting of, for example, a vinyl group, a (meth)acryloyl group, an epoxy group, and an oxetane group.

[0049] In formula (1), X1 are each independently an atom or a functional group bonded to an aromatic ring. Each X1 may be at least one selected from the group consisting of a halogen atom, an alkyl group, a haloalkyl group, an aryl group, a hydroxyl group, a hydroxyalkyl group, an amino group, a carboxyl group, a sulfo group, a nitro group, a cyano group, and an acyl group. Note that m is an integer of 0 to 4. In formula (1), hydrogen atoms are omitted. For example, when m is 0, none of the hydrogen atoms in the aromatic ring in formula (1) is substituted. When m is 1, one hydrogen atom in the aromatic ring is substituted with an atom other than a hydrogen atom.

[0050] The sulfur-containing compound (A1) preferably contains a polyarylene sulfide compound (A12). In the present disclosure, the polyarylene sulfide compound is a compound having a repeating unit represented by the following formula (2) in the molecule.

[0051] [-Ar-S-] (2) In formula (2), -Ar- represents an arylene group. When Ar in formula (2) is phenylene (Ph), compound (A12) may overlap with the compound having a phenyl sulfide skeleton in compound (A11) having an aryl sulfide skeleton described above, that is, compound (A12) may be included in compound (A11).

[0052] When the photopolymerizable component (A) contains the compound (A12), the cured product of the composition (X) can be provided with high heat resistance and chemical resistance. The compound (A12) may have a structural unit other than the repeating unit shown in the above formula (2). The structural unit other than the repeating unit shown in the formula (2) is, for example, a copolymerization component that can be copolymerized with the repeating unit shown in the formula (2). The copolymerization component is not particularly limited, and examples thereof include a component having at least one bond selected from the group consisting of a meta bond, an ether bond, a sulfone bond, a sulfide ketone bond, a biphenyl bond, a substituted phenyl sulfide bond, a trifunctional phenyl sulfide, and a naphthyl bond.

[0053] Specific examples of the sulfur-containing compound (A1) include at least one selected from the group consisting of allylphenyl sulfide, vinylphenyl sulfide, and bis(4-methacryloylthiophenyl)sulfide. In particular, when the compound (A1) contains bis(4-methacryloylthiophenyl)sulfide, odor is unlikely to be generated when an optical component is produced from the composition (X), even though the sulfur-containing compound (A1) has a sulfur atom. Therefore, it is possible to improve the working environment when a cured product is produced from the composition (X) and a light-emitting device 1 including the cured product is produced.

[0054] The percentage of the sulfur-containing compound (A1) relative to the photopolymerizable component (A) is preferably 50% by mass or more. The percentage of the sulfur-containing compound (A1) is more preferably 60% by mass or more. The percentage of the sulfur-containing compound (A1) relative to the photopolymerizable component (A) is, for example, 100% by mass or less, or 85% by mass or less, preferably 80% by mass or less, more preferably 70% by mass or less.

[0055] The boiling point of the sulfur-containing compound (A1) is preferably 200°C or higher, and more preferably 250°C or higher. In this case, the sulfur-containing compound (A1) is unlikely to volatilize from the composition (X) during storage of the composition (X) or when the composition (X) is heated. Therefore, the storage stability of the composition (X) is unlikely to be impaired. In addition, even if the sulfur-containing compound (A1) remains unreacted in the cured product and the optical component 5, outgassing due to the sulfur-containing compound (A1) is unlikely to occur from the cured product and the optical component 5. Therefore, gaps due to outgassing are unlikely to occur in the light-emitting device 1, for example, between the sealing material 51 and the passivation layer 61. If there are gaps in the light-emitting device 1, moisture may reach the light-emitting element 4 through the gaps, but if there are few gaps, moisture is unlikely to reach the light-emitting element 4, and the light-emitting element 4 is unlikely to deteriorate due to moisture. The boiling point is a boiling point under normal pressure obtained by converting the boiling point under reduced pressure, and is determined, for example, by the method shown in Science of Petroleum, Vol. II, p. 1281 (1938). The boiling point of the sulfur-containing compound (A1) is more preferably -20°C or higher, even more preferably -10°C or higher, and particularly preferably 5°C or higher.

[0056] The viscosity of the sulfur-containing compound (A1) at 25°C is preferably 40 mPa·s or less. In this case, the sulfur-containing compound (A1) can reduce the viscosity of the composition (X). The viscosity of the sulfur-containing compound (A1) at 25°C is more preferably 25 mPa·s or less, and even more preferably 25 mPa·s or less. The viscosity of the sulfur-containing compound (A1) at 25°C is, for example, 1 mPa·s or more, and preferably 3 mPa·s or more.

[0057] The sulfur-containing compound (A1) preferably contains a polyfunctional compound having two or more (meth)acryloyl groups in one molecule. In this case, the sulfur-containing compound (A1) can increase the glass transition temperature of the cured product, and therefore the heat resistance of the cured product and the optical component 5 can be improved.

[0058] It is also preferred that the photopolymerizable component (A) contains a nitrogen-containing compound (A2) having at least one nitrogen atom in one molecule. In this case, the adhesion between the cured product and the optical component 5 and the inorganic material member such as the passivation layer 6 is improved. Therefore, a gap is unlikely to occur between the optical component 5 and the inorganic material member, and moisture is unlikely to penetrate into the light-emitting element 4 through the gap.

[0059] The nitrogen-containing compound (A2) also has photopolymerizability. That is, the nitrogen-containing compound (A2) has, for example, at least one nitrogen atom in one molecule and one or more (meth)acryloyl groups in one molecule. Specific examples of the compound (A2) include at least one selected from the group consisting of acryloylmorpholine, hydroxyethylacrylamide, diethylacrylamide, dimethylaminopropylacrylamide, and pentamethylpiperidyl methacrylate. In the photopolymerizable component (A), the sulfur-containing compound (A1) and the nitrogen-containing compound (A2) are defined by the type of atoms contained in one molecule. Therefore, the compounds contained in the nitrogen-containing compound (A2) and the compounds contained in the sulfur-containing compound (A1) may overlap.

[0060] The refractive index of the nitrogen-containing compound (A2) at 25° C. is preferably from 1.40 to 1.60, more preferably from 1.46 to 1.56, and even more preferably from 1.48 to 1.53.

[0061] The percentage of the nitrogen-containing compound (A2) relative to the total amount of the photopolymerizable component (A) is preferably 50% by mass or less, more preferably 40% by mass or less, and also preferably 10% by mass or more, more preferably 20% by mass or more.

[0062] When the photopolymerizable component (A) contains a sulfur-containing compound (A1) and a nitrogen-containing compound (A2), the mass ratio of the total amount of the sulfur-containing compound (A1) and the nitrogen-containing compound (A2) to the total amount of the composition (X) is preferably 20 mass% or more. In this case, the refractive index can be sufficiently increased. The mass ratio of the total amount of the sulfur-containing compound (A1) and the nitrogen-containing compound (A2) to the total amount of the composition (X) is more preferably 25 mass% or more, and even more preferably 50 mass% or more.

[0063] The photopolymerizable component (A) may contain a photopolymerizable acrylic compound (A3) other than the sulfur-containing compound (A1) and the nitrogen-containing compound (A2) described above. The sulfur-containing compound (A1) and the nitrogen-containing compound (A2) are defined only by the type of atoms in the molecular skeleton or the structure in the molecular skeleton, but the compounds contained in the acrylic compound (A3) are distinguished from the compounds contained in the compounds (A1) and (A2).

[0064] The acrylic compound (A3) contains, for example, at least one compound selected from the group consisting of di(meth)acrylic acid esters of alkylene glycols, di(meth)acrylic acid esters of polyalkylene glycols, and di(meth)acrylic acid esters of alkylene oxide-modified alkylene glycols.

[0065] The number of carbon atoms of the alkylene glycol in the di(meth)acrylic acid ester of alkylene glycol is preferably 2 to 12, more preferably 4 to 12. The alkylene glycol may be linear or may have a branch such as 1,3-butylene glycol and neopentyl glycol. In particular, the di(meth)acrylic acid ester of alkylene glycol preferably contains at least one compound selected from the group consisting of 1,4-butanediol diacrylate, 1,3-butylene glycol diacrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, 1,4-butanediol dimethacrylate, 1,3-butylene glycol dimethacrylate, neopentyl glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, and 1,12-dodecanediol dimethacrylate.Examples of di(meth)acrylic acid esters of alkylene glycol include Sartomer's product number SR213, Osaka Organic Chemical Industry's product number V195, Sartomer's product number SR212, Sartomer's product number SR247, Kyoei Chemical Industry's product name Light Acrylate NP-A, Sartomer's product number SR238NS, Osaka Organic Chemical Industry's product number V230, Daicel's product number HDDA, Kyoei Chemical Industry's product number 1,6HX-A, Osaka Organic Chemical Industry's product number V260, Kyoei Chemical Industry's product number 1,9-ND-A, Shin-Nakamura Chemical Industry's product number A-NOD-A, Sartomer's product number CD595, Sartomer's product number SR238NS, Osaka Organic Chemical Industry's product number V230, Daicel's product number HDDA, Kyoei Chemical Industry's product number 1,6HX-A, Osaka Organic Chemical Industry's product number V260, Kyoei Chemical Industry's product number 1,9-ND-A, Shin-Nakamura Chemical Industry's product number A-NOD-A, and Sartomer's product number CD595. It is preferable to contain at least one compound selected from the group consisting of product number SR214NS, product number BD from Shin-Nakamura Chemical Co., Ltd., product number SR297 from Sartomer, product number SR248 from Sartomer, product name Light Ester NP from Kyoei Chemical Co., Ltd., product number SR239NS from Sartomer, product name Light Ester 1,6HX from Kyoei Chemical Co., Ltd., product number HD-N from Shin-Nakamura Chemical Co., Ltd., product name Light Ester 1,9ND from Kyoei Chemical Co., Ltd., product number NOD-N from Shin-Nakamura Chemical Co., Ltd., product name Light Ester 1,10DC from Kyoei Chemical Co., Ltd., product number DOD-N from Shin-Nakamura Chemical Co., Ltd., and product number SR262 from Sartomer.

[0066] The number of carbon atoms of the alkylene glycol in the di(meth)acrylic acid ester of polyalkylene glycol is, for example, 2 to 4. The polyalkylene glycol includes, for example, at least one selected from the group consisting of polyethylene glycol, polypropylene glycol, and polytetramethylene glycol. The larger the carbon number of the polyalkylene glycol, the higher the hydrophobicity of the cured product and the optical component 5, and the less moisture is allowed to permeate the optical component 5. Therefore, it is particularly preferable that the polyalkylene glycol is propylene glycol. The degree of polymerization of the alkylene glycol is, for example, 2 to 7, preferably 2 to 6, and also preferably 2 to 3. It is particularly preferable that the di(meth)acrylic acid ester of polyalkylene glycol contains at least one compound selected from the group consisting of diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, hexaethylene glycol dimethacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tripropylene glycol dimethacrylate, and tritetramethylene glycol diacrylate. In addition, it is preferable that the di(meth)acrylic acid ester of polyalkylene glycol contains at least one compound selected from the group consisting of Sartomer Corporation product number SR230, Sartomer Corporation product number SR508NS, Daicel Corporation product number DPGDA, Sartomer Corporation product number SR306NS, Daicel Corporation product number TPGDA, Osaka Organic Chemical Industry Co., Ltd. product number V310HP, Shin-Nakamura Chemical Co., Ltd. product number APG200, Kyoei Chemical Industry Co., Ltd. product name Light Acrylate PTMGA-250, Sartomer Corporation product number SR231NS, Kyoei Chemical Industry Co., Ltd. product name Light Ester 2EG, Sartomer Corporation product number SR205NS, Kyoei Chemical Industry Co., Ltd. product name Light Ester 3EG, Mitsubishi Chemical Corporation product name Acrylate HX, and Shin-Nakamura Chemical Co., Ltd. product number 3PG.

[0067] The di(meth)acrylic acid ester of alkylene oxide modified alkylene glycol includes, for example, propylene oxide modified neopentyl glycol. The di(meth)acrylic acid ester of alkylene oxide modified alkylene glycol includes, for example, EBECRYL145 manufactured by Daicel Corporation.

[0068] The photopolymerizable compound (A) may further contain a polyfunctional acrylic compound (A4) other than the above-mentioned compounds (A1), (A2), and (A3). The polyfunctional acrylic compound (A4) has two or more (meth)acryloyl groups in one molecule. The polyfunctional acrylic compound (A4) can increase the glass transition temperature of the cured product, and therefore can increase the heat resistance of the cured product and the optical component 5. The polyfunctional acrylic compound (A4) contains at least one component selected from the group consisting of, for example, di(meth)acrylic acid esters of polyalkylene glycol, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate, and triethylene glycol diacrylate. The di(meth)acrylic acid ester of polyalkylene glycol having a refractive index higher than 1.459 can contain, for example, at least one compound selected from the group consisting of tetraethylene glycol diacrylate (polyethylene glycol 200 diacrylate), nonaethylene glycol diacrylate (polyethylene glycol 400 diacrylate), and tetraethylene glycol dimethacrylate (polyethylene glycol 200 dimethacrylate).

[0069] The boiling point of the polyfunctional acrylic compound (A4) is preferably 270°C or higher. In this case, the polyfunctional acrylic compound (A4) is unlikely to volatilize from the composition (X) during storage of the composition (X) or when the composition (X) is heated. Therefore, the storage stability of the composition (X) is unlikely to be impaired. In addition, even if the polyfunctional acrylic compound (A4) remains unreacted in the cured product and the optical component 5, outgassing due to the polyfunctional acrylic compound (A4) is unlikely to occur from the cured product and the optical component 5. Therefore, gaps due to outgassing are unlikely to occur in the light-emitting device 1, for example, between the optical component 5 and the passivation layer 6. If there are gaps in the light-emitting device 1, moisture may reach the light-emitting element 4 through the gaps, but if there are few gaps, moisture is unlikely to reach the light-emitting element 4, and the light-emitting element 4 is unlikely to deteriorate due to moisture. It is more preferable that the boiling point of the polyfunctional acrylic compound (A4) is 280°C or higher. The boiling point of the polyfunctional acrylic compound (A4) is defined the same as the boiling point of the sulfur-containing compound (A1).

[0070] The photopolymerizable component (A) may contain a compound (A5) having three or more (meth)acryloyl groups in one molecule. The compound (A5) is defined only by the number of (meth)acryloyl groups in one molecule. Therefore, the compounds contained in each of the acrylic compound (A3) and the polyfunctional acrylic compound (A4) may overlap with the compounds contained in the compound (A5).

[0071] The compound (A5) may contain, for example, at least one selected from the group consisting of trimethylolpropane triacrylate and trimethylolpropane trimethacrylate. When the photopolymerizable component (A) contains the compound (A5), the compound (A5) can increase the glass transition temperature of the cured product, and therefore the heat resistance of the cured product and the optical component 5 can be particularly improved.

[0072] When the photopolymerizable component (A) contains the compound (A5), the percentage of the compound (A5) relative to the photopolymerizable component (A) is preferably more than 0% by mass and not more than 25% by mass. The percentage of the compound (A5) is more preferably 10% by mass or more. In this case, the glass transition temperature of the cured product can be particularly increased. In addition, when the compound (A5) is 25% by mass or less, the viscosity of the composition (X) is unlikely to increase due to the compound (A5). When the percentage of the compound (A5) is 20% by mass or less, the viscosity of the composition (X) is particularly unlikely to increase.

[0073] The photopolymerizable component (A) may contain a monofunctional acrylic compound (A6) having only one (meth)acryloyl group in one molecule. The monofunctional acrylic compound (A6) can suppress the shrinkage of the composition (X) during curing. The monofunctional acrylic compound (A6) can also contribute to reducing the viscosity of the composition (X). However, since the monofunctional acrylic compound (A6) easily increases the refractive index of the composition (X), in order to lower the refractive index of the composition (X), it is preferable that the acrylic compound (A) does not contain the monofunctional acrylic compound (A6), or that the amount of the monofunctional acrylic compound (A6) in the acrylic compound (A) is such that the refractive index of the composition (X) is not excessively increased. When the photopolymerizable component (A) contains the monofunctional acrylic compound (A6), the amount of the monofunctional acrylic compound (A6) relative to the total amount of the photopolymerizable component (A) is preferably more than 0% by mass and not more than 30% by mass. When the amount of the monofunctional acrylic compound (A6) is more than 0 mass%, the shrinkage during curing of the composition (X) can be suppressed. When the amount of the monofunctional acrylic compound (A6) is 30 mass% or less, outgassing of the composition (X) due to the monofunctional acrylic compound (A6) is unlikely to occur.

[0074] Examples of the monofunctional acrylic compound (A6) include tetrahydrofurfuryl acrylate, isobornyl acrylate, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, isobutyl acrylate, t-butyl acrylate, isooctyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, 3-methoxybutyl acrylate, ethoxyethyl acrylate, butoxyethyl acrylate, ethoxydiethylene glycol acrylate, methoxydiethyl acrylate, and the like. Silethyl acrylate, ethyl diglycol acrylate, cyclic trimethylolpropane formal monoacrylate, imide acrylate, isoamyl acrylate, ethoxylated succinic acid acrylate, trifluoroethyl acrylate, ω-carboxypolycaprolactone monoacrylate, cyclohexyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, stearyl acrylate, diethylene glycol monobutyl ether acrylate, lauryl acrylate, isodecyl acrylate, 3,3,5-trimethylcyclo Hexanol acrylate, isooctyl acrylate, octyl / decyl acrylate, tridecyl acrylate, caprolactone acrylate, ethoxylated (4) nylphenol acrylate, methoxypolyethylene glycol (350) monoacrylate, methoxypolyethylene glycol (550) monoacrylate, phenoxyethyl acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl acrylate, methylphenoxyethyl acrylate acrylate, 4-t-butylcyclohexyl acrylate, caprolactone modified tetrahydrofurfuryl acrylate, tribromophenyl acrylate, ethoxylated tribromophenyl acrylate, 2-phenoxyethyl acrylate, ethylene oxide adduct of 2-phenoxyethyl acrylate, propylene oxide adduct of 2-phenoxyethyl acrylate, isobornyl acrylate, dicyclopentanyl acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 1,Contains at least one compound selected from the group consisting of 4-cyclohexanedimethanol monoacrylate, 3-methacryloyloxymethylcyclohexene oxide, and 3-acryloyloxymethylcyclohexene oxide.

[0075] It is also preferred that the compound (A1) contains a compound (A7) having silicon in the molecular skeleton. In this case, the adhesion between the cured product and the optical component 5 and the inorganic material member is improved. Therefore, a gap is unlikely to occur between the optical component 5 and the passivation layer 6, and moisture is unlikely to penetrate into the light-emitting element 4 through the gap.

[0076] In addition, the compound (A7) is defined only by the type of atoms in the molecular skeleton, and therefore the compounds included in each of the compounds (A1), (A2), (A3), (A4), (A5) and (A6) may overlap with the compounds included in the compound (A7).

[0077] The compound having silicon in its molecular skeleton contains at least one compound selected from the group consisting of, for example, 3-(trimethoxysilyl)propyl acrylate (e.g., product number KBM5103 manufactured by Shin-Etsu Chemical Co., Ltd.) and (meth)acrylic group-containing alkoxysilane oligomer (e.g., product number KR-513 manufactured by Shin-Etsu Chemical Co., Ltd.). The boiling point of the compound having silicon in its molecular skeleton is preferably 270°C or higher. In addition, it is also preferable that the compound having silicon in its molecular skeleton is a polyfunctional compound. For this reason, it is particularly preferable that the compound having silicon in its molecular skeleton contains a (meth)acrylic group-containing alkoxysilane oligomer.

[0078] When the photopolymerizable component (A) contains a compound (A7) having silicon in its molecular skeleton, the percentage of the compound (A7) having silicon in its molecular skeleton relative to the photopolymerizable component (A) is preferably 0.1% by mass or more, more preferably 1% by mass or more. It is also preferable that the percentage of the compound having silicon in its molecular skeleton is 20% by mass or less.

[0079] The composition (X) may further contain a radical polymerizable compound (E) other than the compounds described above. The radical polymerizable compound (E) may contain either one or both of a polyfunctional radical polymerizable compound (E1) having two or more radical polymerizable functional groups in one molecule and a monofunctional radical polymerizable compound (E2) having only one radical polymerizable functional group in one molecule. The amount of the radical polymerizable compound (E) relative to the total amount of the acrylic compound (A) and the radical polymerizable compound (E) is, for example, 10 mass% or less. The polyfunctional radical polymerizable compound (E1) may contain at least one compound selected from the group consisting of aromatic urethane oligomers, aliphatic urethane oligomers, epoxy acrylate oligomers, polyester acrylate oligomers, and other special oligomers having two or more ethylenic double bonds in one molecule. The monofunctional radically polymerizable compound (E2) contains at least one compound selected from the group consisting of, for example, N-vinylformamide, vinylcaprolactam, vinylpyrrolidone, phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, allyl glycidyl ether, 1,2-butylene oxide, 1,3-butadiene monoxide, 1,2-epoxydodecane, epichlorohydrin, 1,2-epoxydecane, styrene oxide, cyclohexene oxide, 3-vinylcyclohexene oxide, 4-vinylcyclohexene oxide, N-vinylpyrrolidone, and N-vinylcaprolactam.

[0080] The photopolymerization initiator (B) is not particularly limited as long as it is a compound that generates radical species when irradiated with ultraviolet light. The photopolymerization initiator (B) contains at least one compound selected from the group consisting of, for example, aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, thio compounds (thioxanthone compounds, thiophenyl group-containing compounds, etc.), hexaarylbiimidazole compounds, ketoxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having carbon-halogen bonds, and alkylamine compounds. The amount of the photopolymerization initiator (B) relative to 100 parts by mass of the composition (X) is, for example, 1 part by mass or more and 20 parts by mass or less.

[0081] The photopolymerization initiator (B) may contain a sensitizer as a part of the photopolymerization initiator (B). The sensitizer can promote the radical generation reaction of the photopolymerization initiator (B) to improve the reactivity of the radical polymerization and improve the crosslink density. The sensitizer may contain at least one compound selected from the group consisting of, for example, 9,10-dibutoxyanthracene, 9-hydroxymethylanthracene, thioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, anthraquinone, 1,2-dihydroxyanthraquinone, 2-ethylanthraquinone, 1,4-diethoxynaphthalene, p-dimethylaminoacetophenone, p-diethylaminoacetophenone, p-dimethylaminobenzophenone, p-diethylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, p-dimethylaminobenzaldehyde, and p-diethylaminobenzaldehyde.

[0082] The content of the sensitizer in the composition (X) is, for example, 0.1 to 5 parts by mass, preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the solid content of the composition (X). When the content of the sensitizer is within such a range, the composition (X) can be cured in air, and it is not necessary to cure the composition (X) in an inert atmosphere such as a nitrogen atmosphere.

[0083] The composition (X) may contain a polymerization accelerator in addition to the photopolymerization initiator (B). The polymerization accelerator contains, for example, an amine compound such as ethyl p-dimethylaminobenzoate, 2-ethylhexyl p-dimethylaminobenzoate, methyl p-dimethylaminobenzoate, 2-dimethylaminoethyl benzoate, or butoxyethyl p-dimethylaminobenzoate.

[0084] Composition (X) may contain components such as additives other than the components described above, so long as the effects of the present disclosure are not impaired.

[0085] For example, the composition (X) may further contain a moisture absorbent (C). When the composition (X) contains the moisture absorbent (C), the cured product of the composition (X) and the optical component can have moisture absorption properties. Therefore, the sealing material 51, which is an optical component, can further prevent moisture from penetrating into the light emitting element 4 in the light emitting device 1. The average particle size of the moisture absorbent (C) is preferably 200 nm or less. In this case, the cured product can have high transparency.

[0086] The moisture absorbent (C) is preferably an inorganic particle having moisture absorbing properties, and preferably contains at least one component selected from the group consisting of, for example, zeolite particles, silica gel particles, calcium chloride particles, and titanium oxide nanotube particles. It is particularly preferable that the moisture absorbent (C) contains zeolite particles.

[0087] Zeolite particles having an average particle size of 200 nm or less can be produced, for example, by pulverizing general industrial zeolite. In producing the zeolite particles, the zeolite may be pulverized and then crystallized by hydrothermal synthesis or the like, in which case the zeolite particles can have particularly high hygroscopicity. Examples of the method for producing such zeolite particles are disclosed in JP 2016-69266 A, JP 2013-049602 A, and the like.

[0088] When the composition (X) contains the moisture absorbent (C), the ratio of the moisture absorbent (C) to the total amount of the composition (X) is preferably 1% by mass or more and 20% by mass or less. If the ratio of the moisture absorbent (C) is 1% by mass or more, the cured product can have particularly high moisture absorption. If the ratio of the moisture absorbent (C) is 20% by mass or less, the viscosity of the composition (X) can be particularly reduced, and the composition (X) can have a sufficiently low viscosity to be applicable by the inkjet method. The ratio of the moisture absorbent (C) is more preferably 3% by mass or more, and particularly preferably 5% by mass or more. The ratio of the moisture absorbent (C) is more preferably 15% by mass or less, and particularly preferably 13% by mass or less.

[0089] When the composition (X) contains the moisture absorbent (C), the composition (X) preferably further contains a dispersant (D). In this case, the dispersant (D) can improve the dispersibility of the moisture absorbent (C) in the composition (X). Therefore, the composition (X) is less likely to suffer from the increase in viscosity and the decrease in storage stability caused by the moisture absorbent (C).

[0090] The dispersant (D) is a surfactant that can be adsorbed to particles. The dispersant (D) has an adsorption group (generally called an anchor) that can be adsorbed to particles, and a molecular skeleton (generally called a tail) that adheres to the particles by the adsorption of the adsorption group to the particles. The dispersant (D) contains at least one component selected from the group consisting of, for example, an acrylic dispersant whose tail is an acrylic molecular chain, a urethane dispersant whose tail is a urethane molecular chain, and a polyester dispersant whose tail is a polyester molecular chain. The adsorption group includes at least one of, for example, a basic polar functional group and an acidic polar functional group. The basic polar functional group includes at least one group selected from the group consisting of, for example, an amino group, an imino group, an amide group, an imide group, and a nitrogen-containing heterocyclic group. The acidic polar functional group includes at least one group selected from the group consisting of, for example, a carboxyl group and a phosphate group. The dispersant (D) may contain at least one compound selected from the group consisting of, for example, the Solsperse series manufactured by Nippon Louvre Resol Co., Ltd., the DISPERBYK series manufactured by BYK-Chemie Japan Co., Ltd., and the AJISPER series manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0091] When the composition (X) contains a moisture absorbent (C), the amount of the dispersant (D) relative to the moisture absorbent (C) is preferably 5 parts by mass or more and 60 parts by mass or less. When the amount of the dispersant (D) is 5 parts by mass or more, the function of the dispersant (D) can be effectively expressed, and when the amount is 60 parts by mass or less, free molecules of the dispersant (D) in the optical component 5 can be prevented from inhibiting the adhesion between the optical component 5 and the member made of an inorganic material. In either case, the amount of the dispersant (D) is more preferably 15 parts by mass or more, more preferably 50 parts by mass or less, even more preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less.

[0092] The composition (X) may contain an inorganic filler other than the moisture absorbent (C), but may not. The composition (X) does not contain an inorganic filler, and even if it does contain an inorganic filler, it is preferable that the amount is such that the viscosity does not increase excessively. In this embodiment, even if it does not contain an inorganic filler for adjusting the refractive index, or the content of the inorganic filler is such that the viscosity does not increase excessively, the refractive index of the cured product of the composition (X) can be increased.

[0093] When the composition (X) contains an inorganic filler, the inorganic filler is preferably a nanoparticle having a high refractive index. In this case, the refractive index of the composition (X) and the cured product of the composition (X) can be further improved. Specific examples of the inorganic filler include zirconia (ZrO2) particles and titanium oxide (TiO2) particles. The proportion of the inorganic filler in the composition (X) is For example, it is preferably 30 mass % or less.

[0094] As already mentioned, it is preferable that the composition (X) does not contain a solvent. In this case, when preparing a cured product from the composition (X), it is not necessary to dry the composition (X) to volatilize the solvent. In addition, the storage stability of the composition (X) is further improved.

[0095] Composition (X) can be prepared by mixing the above-mentioned components. Composition (X) is preferably liquid at 25°C.

[0096] 2. Structure of the light-emitting device The structure of the light emitting device 1 will be described. As already described, the light emitting device 1 includes a light source and an optical component 5 that transmits light emitted by the light source. For example, the light emitting device 1 includes a light emitting element 4, a passivation layer 61 (62) that covers the light emitting element 4, and a sealant 51. In this case, the light emitting element 4 is the light source, the sealant 51 is the optical component 5, and the passivation layer 61 (62) is the inorganic layer 6. The sealant 51 and the passivation layer 61 (62) overlap each other.

[0097] The light-emitting element 4 includes, for example, a light-emitting diode. The light-emitting diode includes, for example, at least one of an organic EL element (organic light-emitting diode) and a micro light-emitting diode. When the light-emitting element 4 includes an organic light-emitting diode, the light-emitting device 1 including the light-emitting element 4 is, for example, an organic EL display. When the light-emitting element 4 includes a micro light-emitting diode, the light-emitting device 1 including the light-emitting element 4 is, for example, a micro LED display. Note that EL is an abbreviation for electroluminescence.

[0098] The optical component 5 is, for example, a sealant 51 (see FIG. 1A) for the light-emitting element 4, and is, for example, an adjustment member (adjustment layer) 55 (see FIG. 1B) for adjusting the refractive index that is overlapped with a layer having a high refractive index. The optical component 5 is, for example, a thin film, and more specifically, a film having a thickness of, for example, 2 μm to 50 μm, or 2 μm to 30 μm.

[0099] A first example of the structure of the light emitting device 1 will be specifically described with reference to Fig. 1. This light emitting device 1 is a top emission type. The light emitting device 1 includes a support substrate 2, a transparent substrate 3 that faces the support substrate 2 with a gap therebetween, a light emitting element 4 on the surface of the support substrate 2 that faces the transparent substrate 3, and a passivation layer 6 and a sealing material 51 that cover the light emitting element 4.

[0100] The support substrate 2 is made of, for example, but not limited to, a resin material. The transparent substrate 3 is made of a material having light-transmitting properties. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate. The light-emitting element 4 includes, for example, a pair of electrodes 41, 43 and an organic light-emitting layer 42 between the electrodes 41, 43. The organic light-emitting layer 42 includes, for example, a hole injection layer 421, a hole transport layer 422, an organic light-emitting layer 423, and an electron transport layer 424, which are stacked in the above order.

[0101] The light emitting device 1 includes a plurality of light emitting elements 4, which form an array 9 (hereinafter referred to as element array 9) on a support substrate 2. The element array 9 also includes a partition 7. The partition 7 is located on the support substrate 2 and separates two adjacent light emitting elements 4. The partition 7 is produced, for example, by forming a photosensitive resin material using a photolithography method. The element array 9 also includes connection wiring 8 that electrically connects the electrodes 43 and the electron transport layers 424 of adjacent light emitting elements 4 to each other. The connection wiring 8 is provided on the partition 7.

[0102] The passivation layer 6 is preferably made of silicon nitride or silicon oxide, and is particularly preferably made of silicon nitride. In the first example shown in FIG. 1A, the passivation layer 6 includes a first passivation layer 61 and a second passivation layer 62. The first passivation layer 61 covers the element array 9 in a state of direct contact with the element array 9, thereby covering the light-emitting element 4. The second passivation layer 62 is disposed on the opposite side of the element array 9 with respect to the first passivation layer 61, and a gap is provided between the second passivation layer 62 and the first passivation layer 61. The sealant 51 is filled between the first passivation layer 61 and the second passivation layer 62. That is, the first passivation layer 61 is interposed between the light-emitting element 4 and the sealant 51 covering the light-emitting element 4.

[0103] Furthermore, a second sealing material 52 is filled between the second passivation layer 62 and the transparent substrate 3. The second sealing material 52 is made of, for example, a transparent resin material. The material of the second sealing material 52 is not particularly limited. The material of the second sealing material 52 may be the same as or different from the sealing material 51.

[0104] The light emitting device 1 may further include an optical component, such as a polarizing plate, between the second passivation layer 62 and the second sealing material 52.

[0105] A second example of the structure of the light emitting device 1 will be described with reference to FIG. 1B. Elements common to the first example shown in FIG. 1A are given the same reference numerals as in FIG. 1A, and detailed descriptions thereof will be omitted as appropriate. The light emitting device 1 shown in FIG. 1B is also of a top emission type. The light emitting device 1 includes a support substrate 2, a transparent substrate 3 facing the support substrate 2 with a gap therebetween, a light emitting element 4 on the surface of the support substrate 2 facing the transparent substrate 3, and a passivation layer 6 and a sealant 51 covering the light emitting element 4. The passivation layer 6 in the light emitting device 1 of the second example includes a first passivation layer 61 and a second passivation layer 62. The second example includes an adjustment layer 55 for adjusting the refractive index that overlaps the second passivation layer 62. The adjustment layer 55 is included in the optical component 5.

[0106] The adjustment layer 55 can make it difficult to refract the light emitted from the light emitting element 4 in the light emitting device 1. Specifically, the adjustment layer 55 can make it difficult to refract the light from the second passivation layer 62, which is a layer with a high refractive index, toward a layer with a lower refractive index when the light emitted from the light emitting element 4 passes through the inorganic layer 6 and the sealing material 51 (specifically, the first passivation layer 61, the sealing material 51, and the second passivation layer 62). The adjustment layer 55 can be made from the ultraviolet curable resin composition of this embodiment. Therefore, the light emitting device 1 can further improve the extraction efficiency of the light emitted from the light emitting element 4. The adjustment layer 55 can make it difficult to reflect the light from the light emitting element 4 at, for example, an interface with a layer with a high refractive index or an interface between a layer with a high refractive index and a layer with a low refractive index, and may be configured so that the light is continuously transmitted or refracted. The shape of the adjustment layer 55 is not particularly limited, but the adjustment layer 55 may have fine irregularities, for example.

[0107] The thickness of the adjustment layer 55 is not particularly limited and may be adjusted appropriately depending on the dimensions of the light emitting device 1 and each component in the light emitting device 1, but may be, for example, 50 nm or more and 5 μm or less.

[0108] 1A are omitted in the second example shown in Fig. 1B, but the light emitting device 1 shown in the second example may include the second sealing material 52 and the transparent substrate 3. The light emitting device 1 shown in the second example may include an optical component such as a polarizing plate.

[0109] 3. Method for manufacturing optical components and light-emitting device A method for producing an optical component 5 using the composition (X) and a method for producing a light emitting device 1 will be described with reference to a light emitting device 1 having a first example structure shown in FIG. 1A.

[0110] In this embodiment, it is preferable to mold the composition (X) by the inkjet method, and then irradiate the composition (X) with ultraviolet light to harden it, thereby producing the sealing material 51. In this embodiment, the composition (X) can be applied and molded by the inkjet method.

[0111] When applying composition (X) by the inkjet method, in the case where composition (X) has a sufficiently low viscosity at room temperature, for example, a viscosity at 25°C of 30 mPa s or less, particularly 15 mPa s or less, composition (X) can be molded by applying it by the inkjet method without heating.

[0112] When the composition (X) has a property of decreasing viscosity by heating, the composition (X) may be heated and then applied by an inkjet method to form the composition (X). When the viscosity at 0°C is 30 mPa·s or less, particularly 15 mPa·s or less, the viscosity of composition (X) can be reduced by simply heating it slightly, and the reduced-viscosity composition (X) can be ejected by the inkjet method. The heating temperature of composition (X) is, for example, 20°C or more and 50°C or less.

[0113] More specifically, for example, first, a support substrate 2 is prepared. On one surface of the support substrate 2, partition walls 7 are fabricated by photolithography using, for example, a photosensitive resin material. Next, a plurality of light-emitting elements 4 are provided on one surface of the support substrate 2. The light-emitting elements 4 can be fabricated by an appropriate method such as a vapor deposition method or a coating method. In particular, it is preferable to fabricate the light-emitting elements 4 by a coating method such as an inkjet method. In this way, an element array 9 is fabricated on the support substrate 2.

[0114] Next, a first passivation layer 61 is provided on the element array 9. The first passivation layer 61 can be formed by a deposition method such as a plasma CVD method.

[0115] Next, the composition (X) is formed on the first passivation layer 61 by, for example, an inkjet method to form a coating film. If the inkjet method is used for both the formation of the light emitting element 4 and the application of the composition (X), the manufacturing efficiency of the light emitting device 1 can be particularly improved. Next, the coating film is cured by irradiating it with ultraviolet light to form the sealing material 51. The thickness of the sealing material 51 is, for example, 5 μm or more and 50 μm or less.

[0116] Next, a second passivation layer 62 is provided on the sealing material 51. The second passivation layer 62 can be formed by a deposition method such as a plasma CVD method.

[0117] Next, an ultraviolet-curable resin material is provided on one surface of the support substrate 2 so as to cover the second passivation layer 62, and then the transparent substrate 3 is placed on the resin material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate.

[0118] Next, ultraviolet light is irradiated from the outside toward the transparent substrate 3. The ultraviolet light passes through the transparent substrate 3 and reaches the ultraviolet-curable resin material. This causes the ultraviolet-curable resin material to cure, and the second sealing material 52 is produced. The second sealing material 52 functions as an adhesive between the second passivation layer 62 and the transparent substrate 3.

[0119] In this embodiment, as described above, it is possible to make it difficult for a decrease in luminous efficiency caused by the passivation layer 6 and the sealing material 51 in the light emitting device 1 to occur.

[0120] The thickness of the sealing material 51 is, for example, 1 μm or more and 20 μm or less. The thickness of the sealing material 51 may be 15 μm or less. In this case, by thinning the sealing material 51, the light emitting device 1 can be thinned, and a flexible light emitting device 1 can be obtained. Even if the thickness of the sealing material 51 is 10 μm or less, in this embodiment, it is possible to prevent a decrease in luminous efficiency caused by the passivation layer 6 and the sealing material 51 in the light emitting device 1 from occurring. It is more preferable that the thickness of the sealing material 51 is 8 μm or less. In order to effectively suppress moisture to the light emitting element 4 by the sealing material 51, the thickness of the sealing material 51 is preferably 3 μm or more, and more preferably 5 μm or more.

[0121] The thickness of the passivation layer 6 overlapping the sealing material 51 is, for example, 0.1 μm or more and 2 μm or less. When the passivation layer 6 includes the first passivation layer 61 and the second passivation layer 62 as described above, it is preferable that the thickness of each of the first passivation layer 61 and the second passivation layer 62 is 0.1 μm or more and 2 μm or less.

[0122] The refractive index of the sealing material 51 is 85% or more and 100% or less of the refractive index of the passivation layer 6. It is preferable that the refractive index of the sealant 51 is equal to or greater than 1.60 and equal to or less than 1.87. For example, when the passivation layer 6 is made of silicon nitride having a refractive index of 1.87, the refractive index of the sealant 51 is preferably equal to or greater than 1.60 and equal to or less than 1.87. In this case, it is possible to particularly prevent a decrease in the luminous efficiency of the light emitting device 1 caused by the passivation layer 6 and the sealant 5. Note that in the present disclosure, the refractive index of each of the sealant 5 and the passivation layer 6 refers to the refractive index at 25° C. for light having a wavelength of 589.3 nm (the D line of sodium).

[0123] Although the case of producing the encapsulant 51 in the light emitting device 1 from the composition (X) has been described above with reference to Fig. 1A, the present invention is not limited to this. That is, the composition (X) can also be used to produce an optical component 5 other than the encapsulant 51 (for example, an adjustment layer 55 shown in Fig. 1B).

[0124] To produce the refractive index adjusting member (adjustment layer 55) shown in FIG. 1B, for example, in the above-mentioned method for producing the light emitting device 1, a second passivation layer 62 may be provided on the sealing material 51, and then the composition (X) may be applied so as to cover the second passivation layer 62. For example, the composition (X) may be applied by forming the composition on the second passivation layer 62 using an inkjet method to produce a coating film. If the inkjet method is used for both the formation of the light emitting element 4 and the application of the composition (X), the production efficiency of the light emitting device 1 can be particularly improved. Next, the coating film is cured by irradiating it with ultraviolet light to produce the adjustment layer 55. This provides the light emitting device 1 having the adjustment layer 55 produced from the composition (X). The light emitting device 1 may further include a second sealing material 52 overlapping the adjustment layer 55, and may further include a transparent substrate 3 overlapping the second sealing material 52. Note that the member overlapping the adjustment layer 55 is not limited to the above.

[0125] The use of the composition (X) according to this embodiment is not limited to the preparation of the sealant 51 for the light-emitting element 4 and the preparation of a member for adjusting the refractive index. The composition (X) can be used to prepare various optical components that transmit the light emitted by the light source. For example, the optical component may be a color resist. That is, for example, a phosphor may be contained in the composition (X), and a color resist in a color filter may be prepared from this composition (X). This color filter can be provided in a display device such as an organic EL display or a micro LED display, which is a light-emitting device. EXAMPLES

[0126] Specific examples of the present disclosure will be presented below, but the present disclosure is not limited to the examples.

[0127] 1. Preparation of the Composition Compositions of the examples and comparative examples were prepared by mixing the components shown in the table below.

[0128] The details of the components shown in the table are as follows. The viscosity of each component was measured using a rheometer (Anton Paar Japan, model number DHR-2) at a temperature of 25°C and a shear rate of 1000 s -1 The values ​​were measured under the following conditions. (Photopolymerizable component) -3G: Multifunctional acrylic compound. Triethylene glycol dimethacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., boiling point 290, viscosity 8 mPa·s. -SR351S: Multifunctional acrylic compound. Trimethylolpropane triacrylate, boiling point above 300℃, viscosity 106mPa·s. -Bis(4-methacryloylthiophenyl)sulfide: Sulfur-containing compound (compound with a phenyl sulfide skeleton). Manufactured by Tokyo Chemical Industry Co., Ltd., refractive index 1.668, viscosity 20 mPa s. -Allyl phenyl sulfide: Sulfur-containing compound (compound with a phenyl sulfide skeleton). Manufactured by Tokyo Chemical Industry Co., Ltd., refractive index 1.585, viscosity 12 mPa s. -Vinyl phenyl sulfide: Sulfur-containing compound (compound with a phenyl sulfide skeleton). Manufactured by Tokyo Chemical Industry Co., Ltd., refractive index 1.599, viscosity 10 mPa· s. -ACMO: Nitrogen-containing compound. Acryloylmorpholine, boiling point 265, viscosity 12 mPa·s. -POB-A: Manufactured by Kyoei Chemical Co., Ltd. Product name: Light Acrylate POB-A. Viscosity 18 mPa·s, refractive index 1.57 (25°C). (Photopolymerization initiator) - Irgacure 907: BASF, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one. -Irgacure TPO: BASF, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0129] 2.Evaluation Test The following evaluation tests were carried out on the examples and comparative examples, and the results are shown in the table below.

[0130] (1) Viscosity at 25℃ The viscosity of the composition was measured using a rheometer (Anton Paar Japan, model number DHR-2) at a temperature of 25°C and a shear rate of 1000 s -1 The measurements were performed under the following conditions.

[0131] (2) 40℃ viscosity The viscosity of the composition was measured using a rheometer (Anton Paar Japan, model number DHR-2) at a temperature of 40 °C and a shear rate of 1000 s -1 The measurements were performed under the following conditions.

[0132] (3) Glass transition temperature The composition was applied to prepare a coating film, and the coating film was then irradiated with 500 mW / cm 2 UV light using an LED-UV irradiator (peak wavelength 385 nm) manufactured by Panasonic Electric Works Sunkus in an air atmosphere. 2 A film with a thickness of 300 μm was produced by photocuring the film under the conditions of 20 seconds of ultraviolet irradiation. The glass transition temperature of a sample cut from this film was measured using a viscoelasticity measuring device (manufactured by Hitachi High-Tech Science Corporation, model number DMA7100).

[0133] (4) Adhesion The composition was applied onto a piece of quartz glass (dimensions 50 mm x 25 mm x 1 mm) to produce a coating film 50 μm thick. Another piece of quartz glass was placed on top of this coating film so that the dimensions of the contact area between the two were 12.5 mm x 25 mm. The coating film was then cured using an LED-UV irradiator (peak wavelength 385 nm) manufactured by Panasonic Electric Works Sunkus. The atmosphere during light irradiation was 500 mW / cm2. 2 The composition was then exposed to ultraviolet light for 20 seconds under the above conditions to be photocured.

[0134] Next, the adhesion strength between the two quartz glass pieces was evaluated according to the following criteria by carrying out a tensile shear test (tensile speed 5 mm / min) in accordance with JIS-K-6850. A: 15MPa or more. B: Less than 15MPa.

[0135] (5) Outgassing The outgassing when the cured product of the composition was heated was sampled by the headspace method and measured by gas chromatography. In detail, 100 mg of the composition was first placed in a headspace vial. Next, the composition was irradiated with ultraviolet light at 500 mW / cm using an LED-UV irradiator (peak wavelength 385 nm) manufactured by Panasonic Electric Works Sunkus. 2 Under the conditions of 1500mJ / cm for 3 seconds 2 The composition was cured by irradiation under the conditions of 100°C, and the vial was then sealed. The composition was then heated at 80°C for 30 minutes, and the gas phase in the vial was then introduced into a gas chromatograph for analysis. As a result, the composition was rated as "A" when the amount of generated gas was 300 ppm or less, "B" when it was more than 300 ppm but less than 500 ppm, and "C" when it was 500 ppm or more.

[0136] (6) Storage stability The composition was left to stand for one month at 40°C under a nitrogen atmosphere. The viscosity of the composition before and after the test was measured using a rheometer (Anton Paar Japan, model DHR-2) at a temperature of 25°C and a shear rate of 1000 s -1 The viscosity change rate was calculated from the results. A rate of change of less than 5% was rated as "A," a rate of change of 5% or more but less than 10% was rated as "B," and a rate of change of 10% or more was rated as "C."

[0137] (7) Inkjet properties (inkjet printability) The composition was placed in the cartridge of an inkjet printer (manufactured by Ricoh, model MH2420), and after confirming that the composition in the cartridge could be discharged from the nozzle of the inkjet printer, the composition was discharged from the nozzle to continuously print a test pattern. As a result, the case where the composition could be discharged for one hour and the discharge operation was stable was rated as "A", the case where the composition could be discharged for one hour but the discharge operation became intermittently unstable was rated as "B", and the case where the nozzle became clogged before one hour had passed since the start of discharge and the composition could no longer be discharged was rated as "C".

[0138] (8) Transmittance The composition was applied to a slide glass S1112 manufactured by Matsunami Co., Ltd. to prepare a coating film, and a resin-coated glass sample having a thickness of 10 μm was prepared. Using an LED-UV irradiator manufactured by CCS Inc., the peak wavelength was 395 nm, and the irradiation was about 100 mW / cm. 2 The film was irradiated with light for 15 seconds under the above conditions to be photocured, to produce a film with a thickness of 10 μm. The atmosphere during the light irradiation was the same as in the above (3). The total light transmittance of this film was measured according to JIS K7361-1, and evaluated according to the following criteria. As a reference, Matsunami slide glass S1112 was used. A: More than 85%. B: Less than 85%.

[0139] (9) Refractive index of resin A resin composition was prepared by mixing the components shown in Table 1. The refractive index of this resin composition at 25°C for light with a wavelength of 589 nm was measured using a multi-wavelength Abbe refractometer DR-M4 manufactured by Atago Co., Ltd. The results obtained by the measurement are shown in Table 1.

[0140] [Table 1] [Explanation of symbols]

[0141] 1 Light emitting device 4 Light emitting element 5. Optical Components

Claims

1. Contains a photopolymerizable component (A) and a photopolymerization initiator (B), The photopolymerizable component (A) contains a sulfur-containing compound (A1) having at least one sulfur atom in one molecule and a compound (A5) having three or more (meth)acryloyl groups in one molecule, The compound (A1) contains a compound (A11) having an aryl sulfide skeleton, The compound (A11) contains at least one selected from the group consisting of allyl phenyl sulfide, vinyl phenyl sulfide, and a compound represented by formula (1), 【Chemistry 1】 R 1 is an organic group, only one of the two R 1 s or each of the two R 1 s is at least one selected from the group consisting of a vinyl group and a (meth)acryloyl group, each X 1 is independently an atom or functional group bonded to an aromatic ring and is a halogen atom, an alkyl group, a haloalkyl group, an aryl group, a hydroxyl group, a hydroxyalkyl group, an amino group, a carboxyl group, a sulfo group, a nitro group, a cyano group or an acyl group, and m is an integer of 0 to 4, the percentage of the compound (A5) relative to the photopolymerizable component (A) is greater than 0% by mass and less than or equal to 25% by mass, The refractive index is 1.53 or more, The viscosity at at least one of 25° C. and 40° C. is 30 mP·s or less; UV curable resin composition.

2. The compound (A1) contains a polyarylene sulfide compound (A12), The ultraviolet-curable resin composition according to claim 1 .

3. The photopolymerizable component (A) contains a nitrogen-containing compound (A2) having at least one nitrogen atom in one molecule. The ultraviolet-curable resin composition according to claim 1 or 2.

4. The total amount of the compound (A1) and the compound (A2) relative to the total amount of the ultraviolet-curable resin composition is 20 mass% or more. The ultraviolet-curable resin composition according to claim 3 .

5. The glass transition temperature of the cured product is 70°C or higher. The ultraviolet-curable resin composition according to claim 1 .

6. A molded product formed by an inkjet method. The ultraviolet-curable resin composition according to claim 1 .

7. A light source and an optical component that transmits light emitted by the light source, The optical component comprises a cured product of the ultraviolet-curable resin composition according to any one of claims 1 to 6. Light emitting device.

8. A method for manufacturing a light emitting device comprising a light source and an optical component that transmits light emitted by the light source, the method comprising the steps of: The method includes forming the ultraviolet-curable resin composition according to any one of claims 1 to 6 by an inkjet method, and then irradiating the ultraviolet-curable resin composition with ultraviolet light to cure the composition, thereby producing the optical component. A method for manufacturing a light emitting device.

Citation Information

Patent Citations

  • Photocuring inkjet ink

    JP2013185040A

  • Resin composition and cured product thereof

    JP2016155998A

  • Photocurable high refractive index resin composition

    JP2019019245A